An Analysis of Sangam Tamil Society’s Ethical Framework as Instructed in Puṟanāṉūṟu - et. al., Dr Manjula M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Puṟanāṉūṟu is a historical document that serves as a record of the rich cultural heritage of the ancient Tamil civilization. It is filled with ethical guidelines that will serve as guidelines to live by till the end of human civilization. Seventeen poems in Puṟanāṉūṟu are considered a part of the Poruṇmoḻikkāñci section. This essay will analyse the ethical guidelines given to rulers on how to rule and to citizens on how to be good citizens.